Microplankton investigations at the fast ice edge and on the Gunnerus Bank in the Antarctic Ocean made on the 25th JARE cruise (abstract) - Taniguchi, Akira; Iwanami, Keisuke; Futatsumachi, Satoru; Hamada, Etuyuki; Naito, Yasuhiko (1986)
P(論文) departmental bulletin paper